Association between close contact history and the risk of COVID-19 in Purwakarta District, Indonesia - Jihan Srikandhia Purnama; Liena Sofiana (Universitas Ahmad Dahlan, 2023)
Background: COVID-19 pandemic is a global problem. One of the risk factors for COVID-19 is close contact, which has a greater risk of being confirmed because virus transmission generally occurs directly through droplets. Based on regional risk zoning mapping, Purwakarta District is categorized as a moderate risk zone, and most of the confirmed cases are caused by a history of close contact. Still, people with a history of close contact only sometimes become established patients. This study aimed to determine the relationship between close contact status and the incidence of COVID-19 in the Purwakarta district year 2020. Method: This study used observational analysis and a cross-sectional study design. The research data is secondary data from the Purwakarta Regency Health Office. Purposive sampling was used to select 2,650 people for the study. The data analysis method used is chi-square. Results: According to the respondents' characteristics, most are in their early adulthood (26.8 %) and male (52.3 %). According to bivariate analysis, there is a p-value = 0.002 relationship between close contact status and the incidence of COVID-19. People with close contact status are 1.040 times more likely than people who do not have close contact status to get COVID-19 (95 % CI = 1.013-1.069). Conclusion: Close contact status is a risk factor for COVID-19 transmission in Purwakarta Regency during 2020.